Clinical course and prevalence of coercive measures: an observational study among involuntarily hospitalised psychiatric patients - Florian Hotzy; Sonja Mötteli; Anastasia Theodoridou; Andres R. Schneeberger; Erich Seifritz; Paul Hoff; Matthias Jäger (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY